Contemporary perspectives on English as a medium of instruction - Kayi-Aydar, Hayriye; Mahalingappa, Laura, 1975- (Contemporary perspectives on learning environments, 2024)
"English Medium Instruction (EMI) is the use of English to teach academic content in countries where English is not the first language. There continues to be a rapid growth in EMI around the globe and there is often official government support for EMI programs or curriculum. The goal of this volume is to explore current perspectives on EMI from empirical data to theoretical considerations in order to identify strengths and shortcomings of EMI programs and/or curricula, defining ideologies, and dominant methodologies in diverse contexts and offer evidence-based implications for classroom practice, policy, and future research. The chapters reflect the voices of diverse groups of people (e.g., content instructors, classroom teachers, college students, parents, teacher educators, etc.) who experience EMI in their current educational environments in different countries"--